FITNESS FOR SERVICE OF CRACK LIKE FLAWS ON PIPE BASED ON API 579 - M. ERLANGGA IBRAHIM (NIM : 13105081); Pembimbing : Prof. Dr. Ir. IGN. Wiratmaja Puja
In oil and gas industry, piping system is very important to transport and distribute oil and gas as its main product. Besides, piping system operates in the dangerous condition or environment and tend to occur degradation to the component. When degradation happenned, it should be summarized whether the components could operates or should be repaired. Then, it needs some methods which can explain the integrity of piping with degradation. This final project analyze fitness for service method for crack like flaws of pipe based on section 9 API 579. This method consist of several complicated steps. In order to ease anlysis, calculation sheet that was capable to process defect data was developed using Microsoft Excel. This calculation sheet is used for determine the integrity of pipe based on assessment procedure level 1 and level 2. As a case study, data from Natural Gas Pipeline Transcanada was used. Crack like flaws was located on the surface flaw perpendicular to circumferential joint with crack length 13.7 in and crack depth 0.22 in. Based on calculation, it was found that pipe does not meet acceptance criteria level 1 and level 2. For the stress analysis with operating pressure 880 psi results safety factor 0.49 which is pipe does not meet acceptance criteria level 3.